2020
DOI: 10.9734/ajsspn/2020/v6i430094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cropping System under Tillage and Mulching on Soil Physical Properties and Water Use Efficiency by Maize (Zea mays L.) in Southern Benin

Abstract: In agriculture, water has become a limiting factor because of the effects of climate change felt by farmers. This situation seriously compromises agricultural production through pockets of drought, delayed and early cessation of rains and then an increase in the length of the dry season. Aims: This study aims to evaluate the effect of tillage and vegetative mulch on soil physical properties and maize water use efficiency in ferralitic soil of southern Benin. Study Design: The Factorial Complete Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similar findings have been reported. Kouelo et al, 2015 reported that membership of a farmer organization is a significant determining factor of the causes of soil fertility in the southern villages of Benin. Access to extension contact which had positive relationship with farmers' perception, also indicate the importance of extension to farmers (Mwakubo et al, 2006 cited by Adeola, 2012).…”
Section: -Discussionmentioning
confidence: 99%
“…Similar findings have been reported. Kouelo et al, 2015 reported that membership of a farmer organization is a significant determining factor of the causes of soil fertility in the southern villages of Benin. Access to extension contact which had positive relationship with farmers' perception, also indicate the importance of extension to farmers (Mwakubo et al, 2006 cited by Adeola, 2012).…”
Section: -Discussionmentioning
confidence: 99%